Vapour–liquid interfacial properties of square-well chains from density functional theory and Monte Carlo simulation. Issue 19 (28th April 2017) - Martínez-Ruiz, Francisco José; Blas, Felipe J.; Moreno-Ventas Bravo, A. Ignacio; Míguez, José Manuel; MacDowell, Luis G.
Abstract : Vapour–liquid surface tension for tangent (open symbols) and vibrating (filled symbols) square-well chains. Abstract : The statistical associating fluid theory for attractive potentials of variable range (SAFT-VR) density functional theory (DFT) developed by [Gloor et al., J. Chem. Phys., 2004, 121, 12740–12759] is used to predict the interfacial behaviour of molecules modelled as fully-flexible square-well chains formed from tangentially-bonded monomers of diameter σ and potential range λ = 1.5 σ . Four different model systems, comprising 4, 8, 12, and 16 monomers per molecule, are considered. In addition to that, we also compute a number of interfacial properties of molecular chains from direct simulation of the vapour–liquid interface. The simulations are performed in the canonical ensemble, and the vapour–liquid interfacial tension is evaluated using the wandering interface (WIM) method, a technique based on the thermodynamic definition of surface tension. Apart from surface tension, we also obtain density profiles, coexistence densities, vapour pressures, and critical temperature and density, paying particular attention to the effect of the chain length on these properties. According to our results, the main effect of increasing the chain length (at fixed temperature) is to sharpen the vapour–liquid interface and to increase the width of the biphasic coexistence region. As a result, the interfacial thickness decreases and the surface tension increases as the molecular chains get longer. The interfacial thickness and surface tension appear to exhibit an asymptotic limiting behaviour for long chains. A similar behaviour is also observed for the coexistence densities and critical properties. Agreement between theory and simulation results indicates that SAFT-VR DFT is only able to predict qualitatively the interfacial properties of the model. Our results are also compared with simulation data taken from the literature, including the vapour–liquid coexistence densities, vapour pressures, and surface tension.